THE DECCAN TRAPS - AN INTERPRETATION IN TERMS OF PROGRESSIVE LITHOSPHERIC FLEXURE IN RESPONSE TO A MIGRATING LOAD - Watts, A; Cox, K (1989)
Structural and geochemical data from the Western Ghats, India have been used to construct an accurate north-south section of the volcanic stratigraphy of the southwest part of the Deccan province. The characteristic style of the section is one of southerly dip, reversing in the extreme south, southward overstep of higher units onto pre-Deccan rocks, and down-dip thinning of individual formations. In contrast, an east-west section shows continuity of essentially horizontal stratigraphic units without overstepping relationships. Previous authors have interpreted these data in terms of the progressive southward migration of the volcanic source as India drifted northwards over a hot-spot now centered beneath Reunion. We have compared the observed stratigraphy to the predictions of a geophysical model based on the flexural response of the continental lithosphere to a migrating volcanic load. The best fit to the observed section is for the structurally lowest part of the modelled sections with an elastic thickness of the lithosphere of 100 km. This value explains the present day width of the Traps in peninsula India, but requires that up to 5.5 km of the upper part of the flank section has been removed by erosion. The origin of the erosion is not clear but, it may be related to flexural rebound following removal of the cone loads that formed along the trace of the plume. The model cannot explain the subsidence of the Traps beneath the shelf off Bombay or the "rim" uplift of the Traps in the Western Ghats. We attribute these modifications of the stratigraphy to vertical movements (uplift and subsidence) that followed rifting of India from the Mascarene Plateau during the Eocene. © 1989.